Aprimoramento na captura de imagens de vasos sanguíneos da membrana corioalantóica (CAM) de embriões de galinha para processamento e cálculo de sua densidade - Silva, Marcelo Klos da (2021)
This work presents the study of the development of a method to improve the observation conditions and improve results in laboratory experiments, from a stereoscopic microscope (magnifying glass), of the embryo chorioallantoic membrane (CAM) in hen eggs. In these experiments, different types of compounds were implanted that alter blood vessel growth factors for both more and less, that is, they cause a change in the density of blood vessels in the affected region. These studies require the quantification of vascularization to compare the stimulatory or inhibitory effects caused by different agents. This quantification must be accurate, objective and consistent, só the images must have greater clarity in the observable aspects and factors that degrade the quality of an image such as: shadow areas, lack of brightness and depth in the visualization, among other factors, must be minimized. For this, first, the main limitations of the magnifying glass lighting system in the acquisition of images from CAMs and from the study of the characteristics of the original light sources of the microscope and alternative light sources, and adding the use of available resources, were observed, an apparatus was developed to improve the quality and control of lighting. To compare the results obtained by the two methods, a grid counting method and a digital processing method, the B-COSFIRE were used in the images obtained to segment and enable the measurement of density variations of captured vessels through the use of fractals. Due to the characteristics of the illumination method proposed and developed for the study of chorioallantoic membranes, a gain in the results was analyzed as more details of the images were observed, all this compared to the images obtained with the original illumination of the microscope used. It became clear that, with better lighting, more subtle vessels stand out, thus ensuring better results for further image analysis and measurement of vessel density within the field of view.